The Effect of Audit Quality on Earnings Management: Evidence from the UK - Li, Danqing (2017)
Audit quality is an important component of information quality in the capital market. It not only measures the capability of audit firms but also reflects the demand of shareholders to reduce the information asymmetry. While earnings management is a common method for managers to obtain personal interests, which may negatively influence the company value. This study aims to examine the effect of audit quality on earnings management of listed companies in the UK. Following the previous researches, the high audit quality should be able to constrain the earnings management. This study will base on a sample of 3,460 firm-year observations that obtained from the UK public listed companies, and Jones (1991) model will be applied. However, the final results cannot reject the null hypothesis due to the small sample size and the inherent limits of the model. Further investigation will be needed in the future studies.